PEMANFAATAN LIMBAH KULIT BUAH MELINJO (GNETUM GNEMON L) MENJADI PRODUK OLAHAN KERIPIK KULIT BUAH MELINJO - Listiawati Listiawati; Novrita Tri Yulvia; Diah Permata Sari; Novi Handayani; Adib Faqih Robbani; Yasril Muluk (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Agro-industry plays a good role over time until now. Various kinds of products have been produced starting from processing tubers, fruits. but not many people know that forest plants which have the Latin name Gnetum gnemon L turned out to be an alternative to increase family income. Gnetum gnemon L is a type of open- seeded plants (Gymnosperms) commonly called Melinjo. These forest plants come from tropical Asia and the Western Pacific. Melinjo trees grow wild in forests with a height of 1200 meters above sea level. Melinjo fruit is usually consumed as a complement to household vegetables. Melinjo fruit that is commonly consumed is melinjo fruits that are young in age and do not yet have a thick inner fruit layer. Meanwhile, it turns out the melinjo fruit that is old or red has many benefits and high nutritional content. The purpose of this activity is to provide understanding to partners in processing and utilizing the skin of melinjo fruit into melinjo fruit skin chips. The target of community service program is addressed to the Head of Sampir Village, Waringin Kurung Sub-District, Serang Regency Banten and the participants are PKK Sampir Village, Waringin Kurung Sub-District, serang Regency, Banten. The method used in this service is (a) socialization and counseling, which is to provide understanding to partners about the use of melinjo rind (b) training, which is to get knowledge about how to process melinjo rind into an agroindustrial product of melinjo fruit peel chips. The results obtained in this training are the enthusiasm of partners for the knowledge and use of the fruit skin of Melinjo and the positive taste and value of partners that agro-industry is another alternative to generate additional family income